Geriatric Rehabilitation and COVID-19: a Case Report - Brika, Marine (SN Compr Clin Med, 2020)
The COVID-19 infection has particularly affected older adults. Clinical observations in this population highlight major respiratory impairment associated with the development or aggravation of the patient’s frailty state. Mr. P is a 93-year-old frail patient, hospitalized after a COVID-19 infection. The assessment process of this patient has been supported by an innovative multi-systemic tool developed in view of the COVID-19 clinical consequences and a systemic evaluation of motor functions by the Frail’BESTest. This process allowed a mixed clinical picture associated with significant respiratory distress (linked with acute respiratory distress syndrome) and an evident motor frailty. The care plan was developed accordingly, and four assessments were done in the same manner until Mr. P returned home. This case report allows us to see a holistic COVID-19 clinical picture, showing the different axes of clinical reasoning to enhance the rehabilitation process. Furthermore, this case report illustrates the importance of rehabilitation in the COVID-19 context.